Systematic Review and Network Meta-Analysis of Noninvasive Brain Stimulation on Dysphagia after Stroke - Lingling Li; Hailiang Huang; Yuqi Jia; Ying Yu; Zhiyao Liu; Xin Shi; Fangqi Wang (Neural Plasticity)
Background. Dysphagia is a common sequelae after stroke. Noninvasive brain stimulation (NIBS) is a tool that has been used in the rehabilitation process to modify cortical excitability and improve dysphagia. Objective. To systematically evaluate the effect of NIBS on dysphagia after stroke and compare the effects of two different NIBS. Methods. Randomized controlled trials about the effect of NIBS on dysphagia after stroke were retrieved from databases of PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang Data, VIP, and CBM, from inception to June 2021. The quality of the trials was assessed, and the data were extracted according to the Cochrane Handbook for Systematic Reviews of Interventions. A statistical analysis was carried out using RevMan 5.3 and ADDIS 1.16.8. The effect size was evaluated by using the standardized mean difference (SMD) and a 95% confidence interval (CI). Results. Ultimately, 18 studies involving 738 patients were included. Meta-analysis showed that NIBS could improve the dysphagia outcome and severity scale (DOSS) score (standard mean difference SMD=1.44, 95% CI 0.80 to 2.08, P<0.05) and the water swallow test score (SMD=6.23, 95% CI 5.44 to 7.03, P<0.05). NIBS could reduce the standardized swallowing assessment (SSA) score (SMD=−1.04, 95% CI -1.50 to -0.58, P<0.05), the penetration-aspiration scale (PAS) score (SMD=−0.85, 95% CI -1.33 to -0.36, P<0.05), and the functional dysphagia scale score (SMD=−1.05, 95% CI -1.48 to -0.62, P<0.05). Network meta-analysis showed that the best probabilistic ranking of the effects of two different NIBS on the DOSS score is rTMS P=0.52>tDCS P=0.48, the best probabilistic ranking of the SSA score is rTMS P=0.72>tDCS P=0.28, and the best probabilistic ranking of the PAS score is rTMS P=0.68>tDCS P=0.32. Conclusion. Existing evidence showed that NIBS could improve swallowing dysfunction and reduce the occurrence of aspiration after stroke, and that rTMS is better than tDCS. Limited by the number of included studies, more large-sample, multicenter, double-blind, high-quality clinical randomized controlled trials are still needed in the future to further confirm the results of this research.